IN VITRO ANTICOAGULANT AND ANTIOXIDANT ACTIVITIES OF PRASAPLAI RECIPE AND ZINGIBER CASSUMUNAR ROXB. EXTRACTS - SUKATI, SURIYAN; JARMKOM, KHEMJIRA; TECHAOEI, SURACHAI; WISIDSRI, NAKUNTWALAI; KHOBJAI, WARACHATE (International Journal of Applied Pharmaceutics, 2019)
Objective: This present study aimed to evaluate the anticoagulant activity and antioxidant properties of Prasaplai recipe (PPR), a Thai traditional medicine, and its major ingredient, Zingiber cassumunar (ZC) Roxb. extracts, seeking new therapeutic purposes for the recipe. Methods: Aqueous extracts of PPR and ZC Roxb. were prepared by hot water decoction technique. The anticoagulant activity of the extracts was evaluated by prothrombin time (PT) and activated partial thromboplastin time (APTT) tests. In addition to anticoagulant activity, total phenol content and antioxidant activity were investigated. Total phenol content was determined using the Folin–Ciocalteu assay. The antioxidant activity was estimated by DPPH radical scavenging activity and ferric reducing antioxidant power assay. Results: The APTT of plasma samples mixed with the PPR and ZC Roxb. extracts was significantly prolonged (p<0.05) at the concentration of 1.0 mg/ml and above comparing to the control (normal saline solution) but was no significantly different for the PT. These results suggested that PPR and ZC Roxb. extracts showed anticoagulant activity affecting the function of coagulation factor in the intrinsic pathway. All aqueous extracts possessed considerable antioxidant activity and were rich in total polyphenol. Conclusion: This finding indicates that the aqueous extracts possess significant anticoagulant and antioxidant activities, thus showing the potential PPR and ZC Roxb. as a new source of bioactive compounds for therapeutic purposes, with particular emphasis on the prevention and treatment of thrombosis.